TIKTOK APPLICATION AS A DA’WAH MEDIA (Analysis of Netizen Perceptions on Social Media Utilization) - Kusuma, Wira Hadi; Resi, Masayu Zahwa (Jurnal Ilmiah Syi'ar, 2023)
This research is motivated by the existence of the tiktok phenomenon which is used as a propaganda medium. The object of this research study is Husain Basyaiban, a da'wah activist using tiktok with the account @basyasman00. This study aims to describe netizens' perceptions of the use of the TikTok application as a da'wah media as well as describe netizens' perceptions of da'wah content on the @basyasman00 account. The method used in this research is qualitative with descriptive techniques. The results of this study indicate that netizens' perceptions of the TikTok application as a da'wah media are influenced by attention, functional, and structural factors. TikTok as a propaganda medium is considered capable of influencing the perceptions of netizens. TikTok is able to become an appropriate and effective forum that can be used by preachers to provide preaching about religion, Islamic law and so on. Meanwhile, netizens' perceptions of da'wah content on the @basyasman00 account consist of three aspects, namely: the cognitive aspect, where netizens receive the da'wah messages delivered by @basyasman00, giving rise to new knowledge and confidence in the content. From the affective aspect, the content created by @basyasman00 is able to balance the negative content on TikTok. The existence of da'wah content @basyasman00 which is also attractively packaged can have a positive effect on netizens. Conative aspects (behavior component), knowledge (knowledge) received by netizens from @basyaman00 content then have a positive effect on netizens. So that it raises the desire to implement it in everyday life.